Employee Retention in Concentrix: Basis for Attrition Reduction Strategies - Toroba, Jamaica Niela Rose H. (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates employee retention at Concentrix-Bridgetowne in Quezon City, Philippines, focusing on the perspectives of both existing and recently resigned employees. In the highly competitive Business Process Outsourcing (BPO) sector, employee turnover presents significant operational and financial challenges. The study explores key factors influencing employee retention, namely job satisfaction, career development opportunities, employee contentment, work-life balance, and compensation and benefits. Utilizing a quantitative descriptive-comparative methodology, the research employed a validated survey instrument and gathered data from 100 respondents—70 current and 30 former employees. Results indicate high levels of employee retention, particularly among existing employees, and reveal statistically significant differences in the perceptions of former and current employees in four out of five key retention dimensions. The only area without a significant difference was work-life balance. The findings underscore the importance of aligning organizational policies with employee expectations, especially in providing clear growth paths and competitive compensation. Based on these insights, a strategic plan was proposed to enhance employee satisfaction and reduce attrition, featuring initiatives across career development, cultural alignment, and compensation benchmarking. The outcomes of this research offer actionable guidance for organizational leaders seeking to improve retention and serve as a reference for future academic inquiries into BPO workforce dynamics.